Differences of Implementation Pharmaceutical Care Standard with Potential Medication Errors Analysis at Several Hospital in Semarang - Satibi Satibi; Vika Marin Y.W.; Sri Suwarni; Kuswardhani Kuswardhani (Faculty of Pharmacy, Universitas Gadjah Mada)
The impact of not implementing good pharmacy service activities are the possiblility of medication errors in the pharmaceutical care process (Depkes, 2014). In fact, most hospitals do not perform pharmaceutical care activities as expected, given some constraints such as the ability of pharmacy, limited knowledge of the hospital management in functions of hospital pharmacy, policy of the hospital management, and the limited knowledge of the relevant parties about hospital pharmacy service. Peraturan Menteri Kesehatan Republik Indonesia nomor 58 Tahun 2014 appeared as a pharmaceutical care standard. This study aims to determine differences of the implementation of pharmaceutical care standard with potential medication errors prescriptions in Government and Private Hospitals in the city of Semarang. The methode used is quasi experiment time approach. The sampling technique used is purposive sampling on an outpatient prescriptions. Subjects were the outpatient prescription in government and private hospitals in Semarang. The analysis used in this study were bivariate analysis Chi square test results obtained administrative requirements x2count = 103,793 and p = 0.000, pharmaceutical requirements showed x2 count = 53,231 and p = 0.000, clinical requirements obtained x2 count = 259,515 and p = 0.000. Based on the three requirements medication errors in prior implementation of pharmaceutical care standard periods was significantly different to the classification of goverment and private hospitals.